KOMUNIKASI DALAM DOMINASI BUDAYA TEORI KRITIS MENURUT JURGEN HABERMAS - A., Agustianto (Universitas Lancang Kuning, 2013)
Jurgen Habermas offers communicative rationality and communicative action as solution on critical theory which is trapped by Marxism basic assumption about human beings. Humans are considered working creatures who always supervise, dominate all cultural aspects. Habermas views that when communication among human beings is forced and is based On irrational tied, it will create cultural domination.